2017
DOI: 10.1002/mp.12230
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the feasibility of classifying breast microcalcifications using photon-counting spectral mammography: A simulation study

Abstract: Simulation results indicated that photon-counting spectral mammography with dual energy material decomposition has the potential to be used as a non-invasive method for discrimination between Type I and Type II microcalcifications that can potentially improve early breast cancer diagnosis and reduce the number of negative breast biopsies. Additional studies using breast specimens and clinical data should be performed to further explore the feasibility of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…The main advantages of PCDs relative to energy‐integrating detectors (EIDs) include rejection of electronic noise, which is important at low exposures, and single‐shot multi‐energy imaging. This latter technique uses a PCD to count detected photons into two or more energy bins, which can be used to estimate volumetric breast density, 3 classify breast calcifications, 4 and remove the source of motion artifacts in contrast‐enhanced breast imaging 2,5 . While such multi‐energy applications are the more exciting prospects of PCDs, PCDs should also be expected to provide image quality equal to or superior to EIDs in standard screening and diagnostic mammography.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of PCDs relative to energy‐integrating detectors (EIDs) include rejection of electronic noise, which is important at low exposures, and single‐shot multi‐energy imaging. This latter technique uses a PCD to count detected photons into two or more energy bins, which can be used to estimate volumetric breast density, 3 classify breast calcifications, 4 and remove the source of motion artifacts in contrast‐enhanced breast imaging 2,5 . While such multi‐energy applications are the more exciting prospects of PCDs, PCDs should also be expected to provide image quality equal to or superior to EIDs in standard screening and diagnostic mammography.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the CNN approach for classification of solid masses and cysts using dual‐energy mammography appears feasible and should be investigated further with clinical data. Results from this and other studies 10,15–18 should motivate further development of spectral mammography systems.…”
Section: Discussionmentioning
confidence: 67%
“…Oncology / Breast, chest: [41,68,76,109,[158][159][160][161][162][163][164] Urology / Abdomen: [53,[165][166][167][168] Orthopaedics / Musculoskeletal: [169][170][171] Normal tissue characterization Measurement of breast density and bone mineral density. Calculation of proton stopping power.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…A pilot study reported a specificity of approximately 50% at a sensitivity level of 1% for discriminating between solids and cysts [41]. Related to cyst-tumour differentiation is differentiation between benign and malignant micro calcifications in the breast, which is initially promising, at least for larger clusters of calcifications [164].…”
Section: Characterization Of Lesions and Abnormalities Without Contra...mentioning
confidence: 99%